POLA INTERAKSI PEDAGOGIS GURU-ANAK DALAM PEMBELAJARAN SENTRA DI TK ALAM ISTIQOMAH KARAWANG - Febrianthy, Cindy; Atin Sahtini, Paulina; Dega, Sayun; Maryamah, Titin; Aryuni, Linda; Armilah , Ai (CBJIS: Cross-Border Journal of Islamic Studies, 2025)
This study aims to describe the pattern of pedagogical interaction between teachers and children in center-based learning at TK Alam Istiqomah Karawang. The research employed a qualitative approach using a descriptive method. Data were collected through documentation of learning activities derived from reports and field notes of university students during their Teaching Practicum (PPL). The analysis focused on teachers’ use of interactional language, particularly prompting questions, across various learning activities and daily habituation practices. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that teacher–child pedagogical interactions in center-based learning are dialogic, reflective, and educative. Teachers consistently use open-ended questions to guide children in understanding rules, managing emotions, and developing social and language skills in a contextual manner. This interaction pattern does not emphasize one-way instruction but encourages children to think, reflect on their behavior, and make independent decisions. Therefore, pedagogical interaction through reflective language plays an essential role in supporting children’s holistic development and aligns with child-centered learning principles in early childhood education.